Risk of low energy availability, disordered eating, and menstrual dysfunction in female collegiate runners - Dambacher, L.; Pritchett, K.; Pritchett, R.; Larson, A. (Journal of Athletic Training, 2025)
Context Collegiate female distance runners may be at risk for low energy availability (LEA) due to increased exercise energy expenditure with or without decreased energy intake. Furthermore, this population has an increased risk of disordered eating (DE), which can lead to LEA and negative health consequences, such as menstrual dysfunction (MD).